Biology, society, and behavior : the development of sex differences in cognition - De Lisi, Richard; McGillicuddy-De Lisi, Ann (Advances in applied developmental psychology ;, 2002)
Applying current theory and research, this book links the development of sex differences in cognition to biological foundations, multiple social processes, and contextual factors. Areas covered include evolutionary biology, neuroscience, social roles, and cultural contextualism to the issues of the onset, causes, and developmental trajectories, as well as patterns in children's and adolescents' thinking, problem-solving, academic performance, and social conditions that are related to behaviors in each of these areas. This edited collection, with chapters by leading scholars, is meant for use by graduate students, researchers, and practitioners in the fields of developmental psychology, cognitive learning and socialization, biology, and education. Language and verbal abilities, mathematical and quantitative abilities, spatial abilities, and social cognition are some of the cognitive domains addressed.